2006
DOI: 10.1007/s10508-005-9000-8
|View full text |Cite
|
Sign up to set email alerts
|

Pictorial Cues and Sexual Desire: An Experimental Approach

Abstract: The cognitive processing of sexual and non-sexual pictorial stimuli was examined to see whether picture rating and recognition tasks have potential utility as a means of assessing levels of sexual desire. Previous research has revealed slower responding to sexual compared to neutral semantic cues in persons with lower self-reported sexual desire. The present study investigated whether sexual pictorial cues evoked a similarly slower responding in people reporting low sexual desire compared to other individuals.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 36 publications
1
10
2
Order By: Relevance
“…Calculating the Pearson r correlation revealed that frequency of sexsomnia per month was not significantly related to level of sexual desire as measured by the HISD, r(31) = .29, p = .112, A t-test revealed no significant difference between scores on the HISD in the current study (M = 65.06, SD = 16.38) and those reported in Conaglen and Evans (2006;M = 67.95, SD = 7.67), t(165) = 1.47, p > .05. Therefore, individuals with sexsomnia did not differ on levels of sexual desire compared with the normative sample.…”
Section: Resultscontrasting
confidence: 59%
See 1 more Smart Citation
“…Calculating the Pearson r correlation revealed that frequency of sexsomnia per month was not significantly related to level of sexual desire as measured by the HISD, r(31) = .29, p = .112, A t-test revealed no significant difference between scores on the HISD in the current study (M = 65.06, SD = 16.38) and those reported in Conaglen and Evans (2006;M = 67.95, SD = 7.67), t(165) = 1.47, p > .05. Therefore, individuals with sexsomnia did not differ on levels of sexual desire compared with the normative sample.…”
Section: Resultscontrasting
confidence: 59%
“…Data reported on the HISD in Conaglen and Evans (2006) were used as a normative comparison for levels of sexual desire. Data reported on the IEMSS in Byers and MacNeil (2006) Study 2 was used as a normative comparison for levels of sexual and relationship satisfaction.…”
Section: Normative Datamentioning
confidence: 99%
“…Nonetheless, self-reported craving is a commonly used proxy and ecological momentary assessments acquired with real-time electronic diaries confirm that exposure to drug cues, and their elicitation of craving states, commonly occur in the minutes and hours before new bouts of stimulant drug use (Epstein et al, 2009). Similarly, in laboratory studies, craving and reward-seeking behavior have been reported to increase following exposure to cues associated with amphetamine (Culbertson et al, 2010; Tolivar et al, 2010), cocaine (Childress et al, 1988, 1993), alcohol (George et al, 2001; Bragulat et al, 2008), cigarettes (Droungas et al, 1995; Carter and Tiffany, 2001; Wray et al, 2011), heroin (Fatseas et al, 2011; Zhao et al, 2012a), and natural rewards such as food (Jansen, 1998; Kelley and Berridge, 2002; Mahler and de Wit, 2010) and sex (Conaglen and Evans, 2006; Kim and Zauberman, in press). …”
Section: Studies In Humans: Subjective and Behavioral Statesmentioning
confidence: 94%
“…Male and female subjects have also been shown to look longer at pornographic slides that they rate more highly arousing (Brown, 1979). Additionally, women with lower sexual arousal have shorter viewing times when evaluating sexual stimuli than women do who report higher levels of sexual arousal (Conaglen & Evans, 2006). In men, higher testosterone is correlated with longer viewing times (Rupp & Wallen, 2007).…”
mentioning
confidence: 99%